(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the pedagogical importance, modern methods, and effectiveness of using gamification technology in English language education. The role of game elements in increasing students’ motivation, improving classroom engagement, and developing communicative skills is highlighted. In addition, the advantages of digital platforms and interactive teaching methods are scientifically substantiated.